Should Holograms Be Displayed Next to Papier-Mâché Models? Reflections on the Conflict of the Pre-Digital and the Post-Digital Museum - Ramirez Gomez, Argenis; Bailey-Ross, Claire (Mimesis Journal, 2024)
The article reflects on the development of interactive artefacts portraying digital scans of taxidermy artefacts and using creative technologies to bring the museum collection to life. The intervention describes two interactive experiences designed to facilitate audience engagement with novel interfaces and the digitalization of Portsmouth’s Cumberland House Natural History Museum store artefacts. We describe the deployment of a dynamic low-cost holographic display of 3D digital models and the showcase of an interactive experience leveraging real-time motion-capturing and Wizard-of-Oz performative methods to animate a conversational holographic animal that engaged with visitors via voice interaction, creating narratives around the museum’s collection.